Perception Of Teaching Skills Development Through Kampus Mengajar Program By English Education Study Program Students Of PGRI Silampari University - Widia Widia; Agus Triyogo; Yulfi Yulfi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research aimed to describe the perception of English education study program students at PGRI Silampari University regarding the development of their teaching skills after participating in the Kampus Mengajar program. This research used a qualitative approach in a qualitative descriptive research design. The research subjects were 15 students of the English Education Study Program at PGRI Silampari University who had participated in the Kampus Mengajar Program batches 4, 5, and 6. The data collection technique used was an open-ended questionnaire. Data obtained from the questionnaire was analyzed using three techniques, namely identification, description, and conclusion. The results of this research showed that students who took the Kampus Mengajar program were able to make good planning and preparation before teaching, present lessons that matched the desired learning outcomes, manage time well and effectively, create a positive classroom climate, enforce class discipline by setting clear and consistent rules, assess student progress properly, and reflect on and evaluate teaching well to develop future teaching skills. In conclusion, students' teaching skills increased after participating in the Kampus Mengajar Program.